Metacognition in Second Language Learning: Strategies, Instruments and Assessment - Bonilla Traña, Mariel (2018)
Learning a second language as it is the case of English, has become a number one necessity in the current world. The complexity of learning a second language owes to the big number of variables that act out in the process, and that inhibit or foster learning. Metacognition and metacognitive strategies constitute relevant mechanisms for learning a second language. This paper, on the one side, discusses the concept of metacognition from the existing models and strategies, and, on the other, from the instruments and training tools that are employed to monitor the participants’ cognitive processes.